2006
DOI: 10.1111/j.1365-2710.2006.00756.x
|View full text |Cite
|
Sign up to set email alerts
|

Metformin–pioglitazone and metformin–rosiglitazone effects on non-conventional cardiovascular risk factors plasma level in type 2 diabetic patients with metabolic syndrome

Abstract: For patients with type 2 diabetes mellitus and metabolic syndrome, combined treatment with metformin and rosiglitazone or pioglitazone is safe and effective, However, the pioglitazone combination also reduced the plasma Lp(a) levels whereas the rosiglitazone combination did not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 35 publications
1
59
0
2
Order By: Relevance
“…In the study by Derosa and cols. (40), the improvement of lipid profile was also significantly greater in the metformin-glimepiride group whereas the reduction of plasma glucose and HbA1c was similar in patients treated with metformin plus glimepiride or metformin plus rosiglitazone. By contrast, in the RECORD study (41) patients treated with rosiglitazone plus metformin or a sulphonylurea achieved significantly lower values of HbA1c as compared to those that received the combination of metformin with a sulphonylurea, but they developed higher weight and LDL-c levels.…”
Section: Discussionmentioning
confidence: 78%
“…In the study by Derosa and cols. (40), the improvement of lipid profile was also significantly greater in the metformin-glimepiride group whereas the reduction of plasma glucose and HbA1c was similar in patients treated with metformin plus glimepiride or metformin plus rosiglitazone. By contrast, in the RECORD study (41) patients treated with rosiglitazone plus metformin or a sulphonylurea achieved significantly lower values of HbA1c as compared to those that received the combination of metformin with a sulphonylurea, but they developed higher weight and LDL-c levels.…”
Section: Discussionmentioning
confidence: 78%
“…It was reported that rosiglitazone and pioglitazone have similar effects on glycemic regulation when these drugs were combined with either metformin or sulfonylurea (Derosa et al 2004(Derosa et al , 2006, but differ in their effects on lipid metabolism. The combination of metformin and sulfonylurea with pioglitazone is associated with significant improvement in lipid and lipoprotein levels, whereas the rosiglitazone does not show any effects on lipid metabolism .…”
Section: Introductionmentioning
confidence: 98%
“…Varios estudios han demostrado la utilidad de metformina en la reducción de los factores de riesgo asociados con diabetes, como el estrés oxidativo, la inflamación endotelial y en la expresión de genes de la inflamación [15][16]22 , sin embargo, hay poca información sobre los efectos de metformina sobre la PCRus. Li et al (2009) 23 demostraron en un modelo de ateroesclerosis de conejo, que al administrar metformina había una disminución de la PCRus, pero también había disminución de la activación de NF-aB.-En los sujetos aquí estudiados no encontramos diferencias en la abundancia del RNAm de NF-aB, sin embargo, el estrés oxidativo está muy ligado a la actividad de este factor nuclear ya que los ROS y los AGEs son inductores de NF-aB 24 , en los sujetos diabéticos estudiados no se encontró diferencias ni en la actividad de la enzima hem oxigenasa-1 ni en la concentración de especies reactivas al ácido tiobarbitúrico, ambos marcadores de estrés oxidativo (datos no mostrados).…”
Section: Discussionunclassified